Supporting Fifth-Grade ELLs' Argumentative Writing Development. (July 2014) - O'Hallaron, Catherine L.
This article reports instruction supporting the development of fifth grade English learners' argumentative writing in an English language arts setting. Arguments analyzed for the study were produced by the same students on two occasions, roughly 3 months apart. In the first instance, students discussed the source text in detail, but were given no genre-specific support for writing. Following professional development, the teacher introduced students to the stages, or structural elements, expected in argumentation, with genre-specific scaffolds. Classroom data illustrate how the teacher scaffolded students' argumentative writing. Analysis of writing data identifies the text- and stage-level features of students' responses, with particular attention paid to students' construction of the reason stage, in which writers must explain why textual evidence supports their overall position on a question about a character or theme. Findings describe the range of responses and point to characteristics of texts and prompt that may influence children's written argumentation.